Optimization with excess electricity management of a PV, energy storage and diesel generator hybrid system using HOMER Pro software - Aysar Yasin; Mohammed Alsayed (Institute of Advanced Engineering and Science, 2020)
In this research, a standalone microgrid power system is proposed to electrify a small agricultural community in Palestinian territories. The load includes residential load and water pumping load. The community comprises about 30 households with some service buildings in addition to the water pumping system. The average load energy demand is 300kWh/day and the average power demand is 12.5kW, in the same context, the average energy demand for water pumping is 49kWh/day. The region has abundant solar radiation potential with a daily average of 5.4 kWh/m2. The optimum design was achieved using the HOMER Pro software. It took into consideration real incident solar radiation data, electrical demand profile for the community and water pumping system and market cost of all equipment. The optimization results showed that the best hybrid system among all feasible configurations is a PV system with an energy storage system combined with a diesel generator. The net present cost of the system is USD636,150 and the cost of energy (COE) produced is USD0.438/kWh. Sensitivity analysis is considered to study the impact of variations in PV cost, diesel fuel price, and maximum annual capacity shortages (MACS), the results showed that MACS has no effects. Energy management procedure is followed to reduce the excess electricity from 10.6% to 6.24% which in turn reduces the COE from 0.438 to USD 0.416/kWh.